471 Pancreatic cancer therapy based on combination of DNA vaccination and PI3Kgamma inhibition. (9th November 2020) - Novelli, Francesco; Curcio, Claudia; Roux, Cecilia; Conti, Laura; Curto, Roberta; Mucciolo, Gianluca; Bulfamante, Sara; Brugiapaglia, Silvia; Scagliotti, Alessandro; Ghigo, Alessandra; Cappello, Paola; Hirsch, Emilio; et al.
Abstract : Background: Pancreatic ductal adenocarcinoma (PDA) is the 4th leading cause of cancer mortality in developed countries, with one of the poorest prognoses among all cancers. Although 10–15% of patients are candidates for gross total surgical resection, recurrence is frequent, and the overall 5-year survival rate is around 8%. Using a proteomic approach, we have identified alpha-Enolase 1 (ENO1) as PDA-associated antigens. We have shown that ENO1 DNA vaccination efficiently prolongs survival of engineered mice that spontaneously develop PDA (both KC and KPC mice). Recently, we have demonstrated that PI3K gamma play a critical role in PDA by driving the recruitment of myeloid derived suppressor cells into tumor tissues and it's genetic or pharmacologic inhibition effectively inhibits PDA progression and metastasis. In this study we assessed the hypothesis that targeting myeloid derived suppressor cells, via pharmacological PI3Kgamma inhibition, synergizes with ENO1 DNA vaccination by inducing a strong and sustained immune response. Methods: KPC mice were vaccinated 4 times with ENO1 starting at 4 weeks of age; 2 weeks after the last immunization mice were treated with the PI3Kgamma inhibitor TG100-115 (2, 5 mg/kg), for further two weeks. At sacrifice neoplastic lesions, immune infiltrate, T and B cell response were analyzed. Results: Mice that received ENO1 and TG100-115 therapy showed a significant decrease in tumor size compared to both ENO1 and PBS treated mice. Moreover, the analysis of pancreas tissues indicated that combined therapy induced an increased number of CD8 and F4/80 cells and a decrease of FoxP3, CD31 and NG2 cells compared to control mice. In addition, we extract mRNA from formalin fixed paraffin embedded pancreas tissues of treated mice. We observed an increase of Granzyme B in both ENO1 and ENO1+TG100-115 and a down modulation of genes involved in fibroblast and stellate cell activation suggesting a modulation of microenvironment in the combined therapy group. Conclusions: Treatment with ENO1 plus TG100-115 is able to reduce tumor size in pancreas, increase immune cell infiltration and modulate stroma cell compartment, making the therapy a suitable approach for PDA treatment. Acknowledgements: This work was supported by grants from the Italian Ministry of Health-Progetti Ricerca Finalizzata (RF-2013-02354892 to FN), Associazione Italiana Ricerca sul Cancro (5 × mille no. 12182 to FN, IG no. 15257 to FN); University of Turin-Progetti Ateneo 2014-Compagnia di San Paolo (PC-METAIMMUN- OTHER to FN and PANTHER to PC), Fondazione Ricerca Molinette Onlus, Fondazione Nadia Valsecchi. Ethics Approval: All animal experiments were approved by the University of Torino, Italian Ministry of Health and performed in accordance with EU laws in the animal facility of the Molecular Biotechnology Center (MBC). Reference no: 378/2015-PR and 597/2019-PR.